Construction of Peer Assessment Instrument to Assess Students’ Character - Sudarto , Agnes Lirinanda; Syamsudin , Amir (KnE Social Sciences, 2019)
Character education is an integral part in elementary education. Elementary teacher utilized variousstrategy to instill good character to the students. Teachers are also expected to assess the students’ character to know its development. Character assessment through observation is limited to a few students per time. therefore, this study aims to construct an appropriate peer assessment instrument to assess characters such as: discipline,and teamwork, as well as understanding the efﬁcacyofpeerassessmentinmeasuringthecharacterofdisciplineandteamwork.Researchdata was obtained by conducting ﬁeld trials in the Elememtary School under the YohanesGabrielFoundation,Surabaya.Resultsfromthisresearchshowedthatpeerassessment was found to be effective to assess the character of discipline and teamwork among grade 5 students of elementary school. Keywords: peer assessment; character of discipline; teamwork.